2016
DOI: 10.5194/amt-9-1671-2016
|View full text |Cite
|
Sign up to set email alerts
|

The potential of clear-sky carbon dioxide satellite retrievals

Abstract: Abstract. Since the launch of the Greenhouse Gases Observing Satellite (GOSAT) in 2009, retrieval algorithms designed to infer the column-averaged dry-air mole fraction of carbon dioxide (X CO 2 ) from hyperspectral near-infrared observations of reflected sunlight have been greatly improved. They now generally include the scattering effects of clouds and aerosols, as early work found that absorption-only retrievals, which neglected these effects, often incurred unacceptably large errors, even for scenes with o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This is because these contaminants can modify the light path seen by the satellite's sensor in ways that are difficult to quantify. Completely neglecting clouds and aerosols in measurements of X CO 2 can result in errors that exceed 1 % (around 4 ppm of CO 2 ) and can be much larger for scenes containing significant contamination (O'Brien and Rayner, 2002;Aben et al, 2007;Butz et al, 2009). Even when scenes are heavily screened to remove clouds and aerosols, a nonscattering retrieval performs 20 %-40 % worse than one that includes some way to account for scattering effects (Nelson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is because these contaminants can modify the light path seen by the satellite's sensor in ways that are difficult to quantify. Completely neglecting clouds and aerosols in measurements of X CO 2 can result in errors that exceed 1 % (around 4 ppm of CO 2 ) and can be much larger for scenes containing significant contamination (O'Brien and Rayner, 2002;Aben et al, 2007;Butz et al, 2009). Even when scenes are heavily screened to remove clouds and aerosols, a nonscattering retrieval performs 20 %-40 % worse than one that includes some way to account for scattering effects (Nelson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, certain tests, where the L2 true state is directly related to the retrieval vector, were simplified by using the older version of the retrieval algorithm which contains a less complicated aerosol scheme. In the older L2 algorithm versions (pre B3.5), the state vector for all soundings always included the same four aerosol types; cloud water, cloud ice, Kahn 1 (a mixture of course and fine mode dust aerosols) and Kahn 2 (carbonaceous 25 mode aerosols) (described more in Nelson et al (2016)). Both Kahn 1 and 2 types contain some sulfate and sea salt aerosols as well.…”
mentioning
confidence: 99%
“…Preprocessor code described in Taylor et al (2016) was run on the cloudy-sky L1b simulations to provide realistic cloud screening prior to running the L2 retrieval.…”
mentioning
confidence: 99%
“…Ignoring scattering altogether, on the other hand, can lead to significant errors in the top-of-the-atmosphere (TOA) radiances, which then leads to errors in the retrieved quantities (Aben et al, 2007;. Nelson et al (2016) have shown that even after filtering for clear-sky conditions, neglecting scattering and absorption by clouds and aerosols can lead to increased errors unless restrictive filtering of the scenes is performed.…”
Section: Introductionmentioning
confidence: 99%